Engineered Escherichia coli cell factory for anthranilate over-production - Kim, Hye-Jin; Seo, Seung-Yeul; Park, Heung-Soon; Ko, Ji-Young; Choi, Si-Sun; Lee, Sang Joung; Kim, Eung-Soo (Frontiers in Microbiology, 2023)
Anthranilate is a key platform chemical in high demand for synthesizing food ingredients, dyes, perfumes, crop protection compounds, pharmaceuticals, and plastics. Microbial-based anthranilate production strategies have been developed to overcome the unstable and expensive supply of anthranilate via chemical synthesis from non-renewable resources. Despite the reports of anthranilate biosynthesis in several engineered cells, the anthranilate production yield is still unsatisfactory. This study designed an Escherichia coli cell factory and optimized the fed-batch culture process to achieve a high titer of anthranilate production. Using the previously constructed shikimate-overproducing E. coli strain, two genes (aroK and aroL) were complemented, and the trpD responsible for transferring the phosphoribosyl group to anthranilate was disrupted to facilitate anthranilate accumulation. The genes with negative effects on anthranilate biosynthesis, including pheA, tyrA, pabA, ubiC, entC, and trpR, were disrupted. In contrast, several shikimate biosynthetic pathway genes, including aroE and tktA, were overexpressed to maximize glucose uptake and the intermediate flux. The rationally designed anthranilate-overproducing E. coli strain grown in an optimized medium produced approximately 4 g/L of anthranilate in 7-L fed-batch fermentation. Overall, rational cell factory design and culture process optimization for microbial-based anthranilate production will play a key role in complementing traditional chemical-based anthranilate production processes.